A Clinical Study of Agnikarma and Navak Guggulu in The Management of Medaja Granthi W.S.R. To Lipoma- A Research Article - Gupta, Mukesh; Dixit, Mahesh; Meena, Hari Mohan; Meena, Namo Narayan (International Research Journal of Ayurveda & Yoga, 2021)
A Lipoma is a benign neoplasm arising from yellow fat. Often it can be hyperplasia or combination of neoplasm and hyperplasia. Deep lipomas are commonly intramuscular. These are common in lower limbs (45 %), trunk (17%), shoulder and upper limb. These are more common in men. Lipomas are found in body of two types of variability, single and multiple. Single lipoma is common. It is usually superficial in subcutaneous area but can be deep also. According to Ayurveda, benign tumors are characterized as Granthi Roga. According to Ayurveda literature, they usually grow in proportion to body fat. These are comparatively large, fatty swellings with Kapha at the root of these tumors, they present as being soft. Vata contributes to the condition, causing the tumors to also have a movable nature. These granthis are of increased itching or tingling nature but less or no pain. Medaja Granthi exudates Ghee (clarified butter) like or white fatty fluid discharge. Ayurveda also implements broad line of management of Granthi Roga like medicinal and para-surgical approach. In Ayurveda, Acharya sushruta has described that Agnikarma is beneficial in Medaja Granthi Roga. There are many oral medications also described by many Acharyas for Medaja Vyadhis.